The Factor in the Technological Creativity of V–VI Formers - Pečiuliauskienė, Palmira; Valantinaitė, Ilona (Pedagogika, 2013)
The article analyses how technological education determines the creativity of 5th–6th formers. Technological education is an integral part of general education. It makes it possible for students to act creatively, to choose flexibly – which is essential for anybody regardless their gender in the constantly changing socio-cultural environment, and to be able to use simple technologies at a user level. The article considers the development of students’ creativity in a systemic approach. Technological education is perceived as a complex of social and educational factors determining students’ creativity. In a creative society creativity is important in all spheres of activity where creative material becomes the basis for competitive advantage in the economy of the global market. The changes in the development of students’ creativity are conditioned by the fluctuation in educational paradigms, learning environments, general education programmes. Creativity is understood as a complex of personal qualities that manifests itself as an ability to offer new ideas, to think non-stereotypically, to orient oneself quickly in problematic situations, to find original solutions easily, which is determined by talents and interests. A systemic approach to creativity requires a systemic assessment of creativity development factors. Technological education is an integral part of general education. It originates from the idea of a “working school”, technologies as a school subject, teaching crafts, polytechnic and professional education. Technologies include material and human intellectual resources, scientific and practical knowledge and ways of organizing work. Technological education can be treated as a complex of both educational and social factors that promote students’ creativity. The method of factor analysis highlighted the following socio-educational factors of 5th–6th formers’ creativity development in technology classes: participation in the activities which are important for the school community; aesthetic activity; communication – cooperation; democratic relations; independent and responsible activity; individual activity; folk art recognition; promotion of activity; group work. Two factors have the most important influence on the development of students’ creativity: participation in the activities which are important for the school community (20.779 percent of dispersion) and participation in aesthetic activity (7.401 percent of dispersion). Nonetheless, the dispersion of social activity is almost three times bigger than that of aesthetic activity. Students’ creativity in technology classes is mostly determined by social factors. Out of the nine distinguished factors as many as four are of social character and only two (group work, individual work) are of educational character. Two creativity factors are related to aesthetic-artistic activity (aesthetic activity, folk art knowledge). Technology teachers see the source of creativity in their students’ interests. The tasks that correspond to students’ interests promote creativity. Technology teachers give a positive evaluation of the influence of individual and group work methods on creativity development. Teachers treat group work methods as a means of creating a favorable learning environment which creates “group enjoyment”. However, teachers state that it is impossible to do without individual work in technology classes. Technological tasks have to be performed accurately, with precision. They require a lot of time. Hence competitive methods are not suitable as competition can diminish the quality of work. Teachers think that in technological education both cooperative learning and individual work are important.